Sosialisasi Pengetahuan dan pemasangan Lampu Penerangan Jalan Umum di Desa Wringinputih Kecamatan Bergas - Arif Rakhman Suharso; Sri Tutie Rahayu; Nurita Widianti; Prijantono Dilyanto; Purwanto Purwanto; Ario Hendartono; Rizka Noor Miftakhul Ulum (Jurnal Nusantara Berbakti, 2025)
Street lighting is one of the important factors in improving the security and safety of Wringinputih Village residents when crossing the road at night, the location of the village is adjacent to the PTPN XVIII Ngobo rubber plantation and the streets around have not been reached by electricity, so the use of solar public street lighting (PJUTS) on the Pluwang-Ngobo highway as an efficient alternative energy solution. Although the initial cost of installation is quite expensive and weather-dependent, these PJUTS lights have an impact on long-term benefits. The installation of these PJUTS lights improves the security and safety of Wringinputih residents, as well as facilitating road access for the community at night